Implementasi CMS Joomla dan Model RAD pada Pusat Transformasi Kebijakan Publik Indonesia - Erick Harlest Budi Raharjo (Prosiding SISFOTEK, 2018)
The role of technology and innovation in providing information greatly affect the circumstances in this digital era, building an information system is a challenge as a benchmark of a company or institution that has the vision and mission to transform an Information. Communities with diverse educational levels of knowledge and experience are in dire need of qualified, accurate information and provide additional knowledge of the latest developments. According to Alan Dennis, Barbara Haley Wixom, David Tegarden (2015: 20): System Development Life Cycle is basically 4 (four) stages: Design, Analysis, Design, and Implementation. RAD is an option in developing information systems at the Indonesian Public Policy Transformation Center. Information system development planning is started by looking at the information system specification that has been running. In the analysis phase, which collects each of the elements as inputs of information needs for the system to be developed. Design, is a phase where designing for physical and soft device architectures between desktop and mobile system information display. Implementation is done after the design phase is fulfilled and Integration becomes the last step until public policy information system is developed. The RAD model was chosen to be one of the methods to improve the service of public policy information system of Indonesia transformasi.org. this public policy information provider service is designed responsivly so that the display will follow the screen of both desktop, smartphone and tablet PC. Conclusions with RAD or Rapid Application Developments are very supportive for the needs of developing a responsive and multiplatform system.